A tension stiffening model for FRCM reinforcements calibrated by means of an extended database. (15th March 2022) - Nerilli, Francesca; Ferracuti, Barbara
Abstract: In the context of the mechanical behavior of the FRCM (Fiber Reinforced Cementitious Matrix) composites as structural retrofitting technique, an accurate analysis of its tensile performance by collecting an extended database of experimental results is presented. The experimental data concern the results of more than 750 tensile tests carried out on FRCM coupons, made with different types of constituent materials (mortar and fiber grid), different geometrical properties and tested with different test set-ups. The data are subdivided into uniform classes and some exclusion criteria are adopted. The influence of the mechanical and geometrical parameters of the constituents on the tensile response of the FRCM reinforcement is assessed. Thus, the relations between the peculiar points of the experimentally-obtained stress–strain law (cracking stress, failure stress, initial elastic modulus, stiffness of the specimens at failure) and the mechanical properties of the constituents are defined. Those relations are the basis to derive an analytical provisional formulation able to reproduce the stress–strain law of the FRCMs, starting from geometrical and mechanical features of the constituents. The proposed tension stiffening model is validated through comparisons with experimental results of FRCM made with different grid types and different mortar nature. Highlights: A large database of available results of tensile tests on FRCM coupons is collected. The tensile performance of Fiber Reinforced Cementitious Matrix is analyzed. The FRCMs tensile response is correlated to the constituents mechanical properties. A tension stiffening model for reproducing the tensile law of the FRCMs is proposed.